Design and characterization of 3-D self-folded microantennas for implantable microdevices - Anacleto, Pedro Alexandre Marques (2020)
Implantable device miniaturization is a cornerstone in modern medicine and the key to unlock new and exciting applications for both monitoring and treatment of diseases. Such miniaturization can be facilitated resorting to miniaturized antennas that will support wireless communications, wireless power transfer (WPT), and energy-harvesting applications. The development of such new miniaturized devices is being supported by innovative fabrication and integration technologies that will lead to challenges in antenna design and characterization. In this article, a miniaturized microantenna produced with a self-folding technique is presented, as well as its characterization challenges. The microcube antenna's geometry (500 × 500 × 500 μm 3 ) is optimized for operation inside biological tissue, and an interface board that allows interfacing the antenna with characterization equipment is presented. The antenna's radiation pattern is obtained both experimentally and numerically, where a good agreement between both the results was achieved.